REPRODUCTIVE AND PHYSIOLOGICAL PARAMETERS OF HEIFERS OF BEEF BREADS IN THE STEPPE AREA OF UKRAINE - Гончарова, І. І. (Scientific Progress & Innovations, 2013)
The results of living mass and reproduced ability of heifers of Znamyanskaya inbreeding type Polissya meat breed with different levels of nursing are presented. Optimum living mass and age of fruitful insemination of heifers is determined. Thus, an intensive rearing of heifers provides daily gain of 700–800 g of living mass, 385 kg in 15–16 months. The results of researches of adaptation of heifers in a pasture period are given. It is experimentally grounded, that absolute indexes which characterize the degree of adaptation plasticity of animals of this breed testify expedience of its breeding in the steppe area of Ukraine.